An Existence Theorem for Differential Inclusions Using the Kurzweil Integral - Macansantos, Priscilla Supnet (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
We define solutions to the differential inclusion x(t) є F(t,x) in the Kurzweil sense, using the Kurzweil integral of a multifunction, and establish an existence theorem for these inclusions under a semicontinuity condition called Property (Q), and the assumption of integrable-boundedness.